2007
DOI: 10.1590/s0034-72992007000400015
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologia do meato médio na rinossinusite crônica

Abstract: Thi s was a prospective study which assessed endoscopically collected middle meatus secretions in patients with chronic rhinosinusitis (CRS) and compared those findings with microbiological data of healthy individuals. Methods: Middle meatus samples were collected from 134 CRS patients. In the laboratory, samples were Gram stained for microscopic examination with white blood cels (WBCs) count and also send for aerobic, anaerobic and fungal cultures. Fifty volunteers served as control. Results: In CRS patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
1
2
1
Order By: Relevance
“…These differences may be due to the use of different transportation and sowing methods. In our study, fungi represented only 1.6% of the cases, similarly to what was reported by Nigro et al 17 ; meanwhile, Araújo et al 19 reported 14%. Cryptococcus is an opportunistic yeast which is occasionally isolated from the paranasal sinuses secretion from AIDS and other immunosupressed patients.…”
Section: Discussionsupporting
confidence: 91%
“…These differences may be due to the use of different transportation and sowing methods. In our study, fungi represented only 1.6% of the cases, similarly to what was reported by Nigro et al 17 ; meanwhile, Araújo et al 19 reported 14%. Cryptococcus is an opportunistic yeast which is occasionally isolated from the paranasal sinuses secretion from AIDS and other immunosupressed patients.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, fungi represented only 1.9% of the microorganisms, while in the study by Araújo they represent 14% 22 . Mitchell mentions that silicofluoride dye for direct …”
Section: Discussioncontrasting
confidence: 64%
“…It is performed by puncture of the maxillary sinus through the canine fossa and using an endoscope, with the collection being performed in the middle meatus. 48 …”
Section: Chronic Rhinosinusitismentioning
confidence: 99%